1981
DOI: 10.1037/0021-843x.90.3.263
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of long-term reaction to rape.

Abstract: To examine long-term reactions to rape, 27 adult women who had been rape victims were interviewed and their current functioning assessed through a variety of written measures. Victims were significantly more depressed and reported less pleasure in daily activities than matched nonvictim controls. Women who had been victims of sudden violent attacks by complete strangers showed the most severe reactions, being even more depressed, fatigued, and fearful, and getting less satisfaction from activities than victims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
1
2

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(79 citation statements)
references
References 7 publications
7
69
1
2
Order By: Relevance
“…The profound and long-term consequences reflect the violent, terrifying and traumatic nature of rape and parallel the responses Mezey development of persistent PTSD is predicted by three offence-related lements: a completed rape, physical injury and the perception of life threat (Kilpatrick et al, 1989), as well as by the failure to show an initial rapid resolution of symptoms within the first two weeks following the assault (Rothbaum et ai, 1992). Apart from PTSD, the most persistent reactions following rape appear to be intense fears of raperelated situations and general diffuse anxiety (Ellis et al, 1981;Kilpatrick étal, 1981;Calhounef al, 1982;Rothbaum et al, 1992). Depression is a common response in the immediate to short term, but appears to be less persistent (Frank & Stewart, 1984).…”
Section: Reactions To Rape (Box 1)mentioning
confidence: 99%
See 1 more Smart Citation
“…The profound and long-term consequences reflect the violent, terrifying and traumatic nature of rape and parallel the responses Mezey development of persistent PTSD is predicted by three offence-related lements: a completed rape, physical injury and the perception of life threat (Kilpatrick et al, 1989), as well as by the failure to show an initial rapid resolution of symptoms within the first two weeks following the assault (Rothbaum et ai, 1992). Apart from PTSD, the most persistent reactions following rape appear to be intense fears of raperelated situations and general diffuse anxiety (Ellis et al, 1981;Kilpatrick étal, 1981;Calhounef al, 1982;Rothbaum et al, 1992). Depression is a common response in the immediate to short term, but appears to be less persistent (Frank & Stewart, 1984).…”
Section: Reactions To Rape (Box 1)mentioning
confidence: 99%
“…Victim-related Prior adjustment problems Sales et al, 1984) Past history of drug or alcohol misuse (Burgess & Holmstrom, 1978) History of prior sexual victimisation (Ellis et al, 1981;Ruch & Chandler, 1983) Assault-related Nature of assault -completed z'. attempted rape Perception of life threat Physical injury (Kilpatrick et al, 1987) Post-assault High levels of distress in the immediate aftermath (Rothbaum et al, 1992) Lack of social support (Norris & FeldmanSummers, 1981;Ruch & Chandler, 1983) Various approaches should be considered depending on the victim's stage of recovery and the nature and extent of the conditions being treated.…”
Section: Box 2 Impediments To Recoverymentioning
confidence: 99%
“…Research has found that women who have experienced multiple episodes of violence are at greater risk of experiencing negative psychosocial outcomes such as PTSD symptoms, poorer adjustment, lifestyle instability, sexual dysfunction, depression, and suicide attempts (Arata, 1999;Banyard, Wiliams & Siegel, 2001;Ellis, Atkeson & Calhoun, 1981;Maker, Kemmelmeier & Peterson, 2001;Miller, Moeller, Kaufman, Divasto, Pathak & Christy, 1978;Miner, Flitter & Robinson, 2006;Nishith, Mechanic & Resick, 2000). There is less research on male victims however.…”
Section: Discussionmentioning
confidence: 99%
“…Aun cuando el tamaño de la muestra no permite hacer generalizaciones con garantías, no cabe duda de que los indicadores obtenidos por Ellis et al (1981) merecen serios estudios de comprobación ulteriores.…”
Section: Impactos De La Violaciónunclassified